DHW + PV: Use of self-consumption photovoltaic surpluses to generate domestic hot water = ACS + FV: Aprovechamiento de excedentes de fotovoltaica de autoconsumo para la generación de agua caliente sanitaria - Style, Oliver; Fulcarà, Vicenç; Clavero, Bega (Building & Management, 2020)
Abstract The implementation of a self-consumption photovoltaic installation in a single-family house with Passivhaus Classic certification is pre-sented. In this case the surpluses of photovoltaic production are diverted to an electrical resistance in the Sanitary Hot Water tank. The system converts electrical energy that is not self-consumed in the home, into thermal energy in the DHW tank for later use. Consumption derived from ACS is often higher than air conditioning in a Passive House, so a solution of this type reduces the energy bill and takes advantage of a renewable energy source to produce hot water, avoiding many of the maintenance problems that solar thermal energy systems usually suffered. Resumen Se presenta la implementación de una instalación fotovoltaica de autoconsumo en una vivienda unifamiliar con certificación Passivhaus Classic, en donde se desvían los excedentes de la producción fotovoltaica a una resistencia eléctrica en el depósito de Agua Caliente Sa-nitaria. El sistema convierte la energía eléctrica que no se autoconsume en la vivienda, en energía térmica en el depósito de ACS para su uso posterior. Los consumos derivados del ACS son a menudo superiores a los de climatización en una Passivhaus, así que una solución de este tipo reduce la factura energética y aprovecha una fuente de energía renovable para producir agua caliente, evitando muchos de los problemas de mantenimiento que suelen sufrir los sistemas de energía solar térmica.